Malaria: disease impacts and long-run income differences - Douglas Gollin; Christian Zimmermann (Institute for the Study of Labor (IZA), 2007)
The World Health Organization (WHO) reports that malaria, a parasitic disease transmitted by mosquitoes, causes over 300 million episodes of acute illness and more than one million deaths annually. Most of the deaths occur in poor countries of the tropics, and especially sub-Saharan Africa. Some researchers have suggested that ecological differences associated with malaria prevalence are perhaps the most important reason why some countries today are rich and others poor. This paper explores the question in an explicit dynamic general equilibrium framework, using a calibrated model that incorporates epidemiological features into a standard general equilibrium framework.
Keywords: 330; Tropenkrankheit; Epidemie; Sozialprodukt; Lebensstandard; Vergleich; Afrika südlich der Sahara